Comprehensive Molecular and Cellular Characterization of Acute Kidney Injury Progression to Renal Fibrosis - Wu, Renyan; Li, Jiawei; Tu, Guowei; Su, Ying; Zhang, Xuepeng; Luo, Zhe; Rong, Ruiming; Zhang, Yi (Frontiers in Immunology, 2021)
Acute kidney injury (AKI) and chronic kidney disease (CKD) represent different stages of renal failure, thus, CKD can be regard as a result of AKI deterioration. Previous studies have demonstrated that immune cell infiltration, oxidative stress, and metabolic mentalism can support renal fibrosis progression in AKI cases. However, the most important triggers and cell types involved in this pathological progression remain unclear. This study was conducted to shed light into the underlying cellular and molecular features of renal fibrosis progression through the analysis of three mouse whole kidney and one human single cell RNA-sequencing datasets publicly available. According to the different causes of AKI (ischemia reperfusion injury [IRI] or cisplatin), the mouse samples were divided into the UIC (control-IRI-unilateral ureteral obstruction [UUO]) and USC (control-cisplatin-UUO) groups. Comparisons between groups revealed eight different modules of differentially expressed genes (DEGs). A total of 1,214 genes showed the same expression pattern in both UIC and USC groups; however, 1,816 and 1,308 genes were expressed specifically in the USC and UIC groups, respectively. Further assessment of the DEGs according to the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment pathway and Gene Ontology (GO) showed that T-cell activation, fatty acid metabolic process and arachidonic acid metabolism were involved in the fibrosis progression in UIC and USC. Single cell RNA-sequencing data along with the collected DEGs information also revealed that the T-cell activation mainly happened in immune cells, whereas the fatty acid metabolic process and arachidonic acid metabolism were occurred in tubule cells. Taken together, these findings suggest that the fibrosis process differed between the UIC and USC stages, in which immune and tubule cells have different functions. These identified cellular and molecular features of the different stages of fibrosis progression may pave the way for exploring novel potential therapeutic strategies in the clinic.